2006
DOI: 10.1577/m04-177.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of River Impoundment and Hatchery Rearing on the Migration Behavior of Juvenile Steelhead in the Lower Snake River, Washington

Abstract: We used radiotelemetry to monitor the migration behavior of juvenile hatchery and wild steelhead Oncorhynchus mykiss as they migrated through Lower Granite Reservoir and Dam on the lower Snake River, Washington. From 1996 to 2001, we surgically implanted radio transmitters in 1,540 hatchery steelhead and 1,346 wild steelhead. For analysis, we used the inverse Gaussian distribution to describe travel time distributions for cohorts (>50 fish) of juvenile steelhead as they migrated downriver. Mean travel rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…Thus, the water withdrawal zone is considered an adverse habitat (Svendsen et al 2010). Second, milling behaviours are coupled with increased risk of predation by wild piscivores Venditti et al 2000;Plumb et al 2006). In the present study, the milling smolts covered a larger area, travelled longer, and spent longer time inside the hydrophone array (Table 1).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, the water withdrawal zone is considered an adverse habitat (Svendsen et al 2010). Second, milling behaviours are coupled with increased risk of predation by wild piscivores Venditti et al 2000;Plumb et al 2006). In the present study, the milling smolts covered a larger area, travelled longer, and spent longer time inside the hydrophone array (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…A number of studies have reported Pacific salmon smolts performing milling behaviours in anthropogenically altered channels (Venditti et al 2000;Plumb et al 2006;Nestler et al 2008). The present study showed that milling behaviours also occur in Atlantic salmon smolts (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 65-rkm distance from the mouth of the Snake River to McNary dam was covered in a median of 5.7 d by the hatchery-origin fish used in this study compared to a median of approximately 2 d for a concurrent study on run-of-river wild subyearling Chinook salmon in the same river reach of the Columbia River basin (Geoff McMichael, Pacific Northwest National Laboratory, unpublished data, 2012). Slower travel times in fish recently released from hatcheries are common [42], [43], [44]. For example, travel rates of wild juvenile steelhead were found to be twice as fast as hatchery-reared steelhead and the hatchery-reared fish were observed moving upstream after release, delaying their seaward migration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Slower travel times in fish recently released from hatcheries are common [42], [43], [44]. For example, travel rates of wild juvenile steelhead were found to be twice as fast as hatchery-reared steelhead and the hatchery-reared fish were observed moving upstream after release, delaying their seaward migration [43]. Behavioral and physiological changes occur in juvenile salmonids during the smoltification period cueing migration to begin.…”
Section: Discussionmentioning
confidence: 99%